Synthesis and Bioassay of Novel Quinozolins (Journal of the College of Basic Education, 2019)
Novel Quinozolins were synthesized in a good yield through convert lacton to lactam and study the biological activity of the synthesized compounds. Quinozolins were characterized by elemental analysis, FT-IR and UV/visible spectra. The novel Quinozolins have been tested in vitro against (gram positive bacteria Staphylococcus aureus and against other gram negative bacteria, such as Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Proteus vulgaris; in order to assess their antimicrobial properties. Moreover, charge, bond length, bond angle, twist angle, heat of formation and steric energy were calculated by using of the ChemOffice program. The study indicates that these Quinozolins have high activity against tested bacteria. Based on the reported results, it may be concluded that the coumarin act as synthons for synthesis of new Quinozolins derivatives through the replacement of oxygen atom by nitrogen atom.